2020
DOI: 10.1111/faf.12448
|View full text |Cite
|
Sign up to set email alerts
|

Density‐dependent growth and survival in salmonids: Quantifying biological mechanisms and methodological biases

Abstract: Understanding the complex variation in patterns of density‐dependent individual growth and survival across populations is critical to adaptive fisheries management, but the extent to which this variation is caused by biological or methodological differences is unclear. Consequently, we conducted a correlational meta‐analysis of published literature to investigate the relative importance of methodological and biological predictors on the shape and strength of density‐dependent individual growth and survival in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 63 publications
1
26
0
Order By: Relevance
“…We considered a DIC difference (ΔDIC) greater than 7 (ΔDIC = DIC of model 1 -DIC of model 2) as sufficient evidence for differences in model fit between two models (Spiegelhalter et al 2002;Cain and Zhang 2019). Constructed models included additive and interactive effects between DD, DI, and RGCT life stage (i.e., immature or mature) because all of these mechanisms have been found to affect instantaneous growth dynamics in salmonid populations (Crozier et al 2010;Kovach et al 2016;Grossman and Simon 2020;Matte et al 2020; see Table 2). Preliminary analyses were conducted based on two scenarios:…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We considered a DIC difference (ΔDIC) greater than 7 (ΔDIC = DIC of model 1 -DIC of model 2) as sufficient evidence for differences in model fit between two models (Spiegelhalter et al 2002;Cain and Zhang 2019). Constructed models included additive and interactive effects between DD, DI, and RGCT life stage (i.e., immature or mature) because all of these mechanisms have been found to affect instantaneous growth dynamics in salmonid populations (Crozier et al 2010;Kovach et al 2016;Grossman and Simon 2020;Matte et al 2020; see Table 2). Preliminary analyses were conducted based on two scenarios:…”
Section: Methodsmentioning
confidence: 99%
“…The biotic and abiotic characteristics of aquatic environments shape the growth dynamics of aquatic ectotherms, and understanding the link between environmental conditions and instantaneous growth can provide valuable information about what limits the productivity of a fish population (O'Gorman et al 2016;Lindmark et al 2018Lindmark et al , 2019. For example, DD effects on instantaneous growth can indirectly affect population growth through size-dependent mortality rates (Post et al 1999;Matte et al 2020). This knowledge is particularly important for managing aquatic ectotherms as the climate continues to change, since DI and DD effects have been shown to affect the size and productivity of many aquatic ectotherm populations (Crozier and Zabel 2006;Daufresne et al 2009;Crozier et al 2010;Sheridan and Bickford 2011;Myrvold and Kennedy 2015;Nelson et al 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Food abundance or consumption was also unrelated to fish somatic growth, mortality, or their trade-off. These results are surprising, given the strong effect of fish density on somatic growth and mortality in the study populations (Matte et al 2020b) and across salmonids in general (Grant and Imre 2005, Martinussen et al 2011, Vincenzi et al 2012, Matte et al 2020a). However, increasing fish density led to increasing competitive intensity through augmented aggression and decreasing distance to neighbors.…”
Section: Discussionmentioning
confidence: 83%
“…Sections were separated by gaps of at least 1 m. All fish were removed from these sections, and YOY trout were stocked to one of four density treatments (0.3, 1, 3 and 7 fish/m 2 ) for a target duration of 21 d (range 9-27 d). These densities encompass those observed across the salmonid literature (Matte et al 2020a), and the natural densities observed in these populations (Matte et al 2020b). Treatments were randomized across sections and years.…”
Section: Experimental Designmentioning
confidence: 99%